2019
DOI: 10.1021/acs.biomac.9b01327
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite Based Ceramic Carrier Promotes Bone Formation in a Femoral Neck Canal Defect in Osteoporotic Rats

Abstract: Hip fractures are among the most common types of fracture risks in old age osteoporotic patients that often end up with immobile disabilities. Weak bones due to loss of mineral content along with an increase in the porosity of the femur neck canal in osteoporosis reduce the mechanical properties of the bone and predispose the patients to fractures. In this study, we have used calcium sulfate/nanohydroxyapatite based nanocement (NC) as carrier of recombinant human bone morphogenetic protein-2 (BMP-2), zoledrona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…In the current study, we have used a ceramic based hydroxyapatite bone substitute as a carrier of two first line anti-tuberculosis drugs, Rifampicin and Isoniazid. The potency of a sulphate hydroxyapatite carrier for bioactive molecules to promote bone healing was established in earlier studies 22 , 26 , 39 41 . Apart from achieving long term sustained release of drugs, it can act as a bone filler material to fill the dead space at the debrided site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we have used a ceramic based hydroxyapatite bone substitute as a carrier of two first line anti-tuberculosis drugs, Rifampicin and Isoniazid. The potency of a sulphate hydroxyapatite carrier for bioactive molecules to promote bone healing was established in earlier studies 22 , 26 , 39 41 . Apart from achieving long term sustained release of drugs, it can act as a bone filler material to fill the dead space at the debrided site.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to use a biphasic CSH/nHAP based nanocement (NC) carrier for local delivery of two first line ATDs (RFP and INH) to achieve the long-term sustained and controlled release. Similar carriers have been previously used as a carrier for bone morphogenetic proteins (BMP) and zoledronic acid (ZA) to promote either the fracture healing 22 24 or enhance the bone mineralization in osteoporotic rats 25 , 26 . To our knowledge, this study is the first to describe the release profile of tuberculosis drugs in a ceramic carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the ALP activity, calcium and collagen production clearly demonstrated that the zirconia/magnesia ceramics possess robust osteoinductive capacity, and thus present great potential for bone tissue engineering applications. In addition, ceramic materials can be used as carriers to deliver cytokines such as bone morphogenetic pro-teins [36], specific osteogenic growth factors that enhance bone formation in vitro [37] and in vivo [33], as well as plasmids for the transfection of bone-forming cells [38], or cement formulations [39] leading to enhanced osteogenic responses. Magnesium-based orthopaedic implants such as pins, plates and screws have been extensively investigated in both small and large animal models, in physiological and osteoporotic models, mainly to observe the degradation pattern of Mg-based implants and the response of peri-implant bone tissue [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of exosomes on enhancing osteoblast differentiation was not observed in a subsequent in vitro study. Qayoom et al (2019) also proposed the role of EVs in a femur neck canal defect model in osteoporotic rats as a biological carrier facilitating bone formation and controlling the dosage of BMP. They used nano cements to deliver BMPs, exosomes, and bisphosphonates, which improved biomechanical strength in the defect.…”
Section: Applications Of Biomaterial-ev Delivery Systems In Btementioning
confidence: 99%